The Influence of Profitability, Audit Fees, and Company Size on Audit Delay with Kap Reputation as a Moderating Variable - Alvina Kayandra Mulia (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This research aims to analyze the influence of profitability, audit fees, and company size on audit delay with the reputation of the Public Accounting Firm (KAP) as a moderating variable in mining sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. This research uses a quantitative approach with an explanatory research design. The research population consisted of 63 mining sector companies, while the sample was determined using a purposive sampling technique to obtain 22 companies with a total of 110 observations. Data were analyzed using descriptive statistics, multiple linear regression, and Moderated Regression Analysis (MRA) with the help of SPSS version 25. The research results showed that profitability and company size had an effect on audit delay, while audit fees did not show a significant effect. These findings indicate that companies with better financial performance and larger business scales tend to complete the audit process more quickly. In addition, KAP reputation is proven to strengthen the influence of profitability on audit delay, but is unable to moderate the influence of audit fees or company size. This research provides an empirical contribution that the auditor's reputation plays an important role in improving the timeliness of financial reporting, especially in companies that have a high level of profitability.